Some Biological Aspects Of Gerres Filamentosus (Cuvier, 1829) In Merbok Estuary, Kedah, Peninsular Malaysia - Noor, Nurul Shafikah Mohd (2013)
Some biological aspects of Gerres filamentosus in Merbok estuary were studied from January to December 2011 using samples from monthly catches. Each sample consists of 50-100 fishes which varied from the smallest (10.1 cm) to the largest (18.3 cm) sizes. The length-weight relationship was analyzed for G. filamentosus by substituting the fish length and weight values into W=aLb. The calculated lengthweight relationships of W=0.011L3.154 and W=0.013L3.103 , obtained from female and male respectively. The exponent value, b = 3.154 for female and b = 3.103 for male showed that both male and female of G. filamentosus had positive allometric growth. Besides, the relative condition factor (Kn) obtained was 0.999±0.074SD and 1.002±0.080SD for female and male, had revealed that male had a better condition than female, at the same time proved that Merbok estuary was in good ambience for survival and favorable for this species. Moreover, the sex ratio was found to be 1:1.45 (male:female). The reproductive cycle of this species was analyzed using the gonadosomatic index, through macroscopic observation and histological method. The maturity stages of male and female G.filamentosus were classified into four stages of testes and five stages of ovary. Herein, G. filamentosus spawn throughout the year with two spawning peaks, one in October 2011 and the second one in February 2011, which coincided with the primary maximum (September to November) and primary minimum (January to February) of rainfall.